2015
DOI: 10.1177/1751143715583861
|View full text |Cite
|
Sign up to set email alerts
|

A calibrated measuring tape accurately predicts tidal volumes from ulna length

Abstract: Usage of a calibrated measuring tape produced accurate estimates of tidal volumes required for lung protective ventilation in healthy volunteers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
2
2
0
Order By: Relevance
“…However, tape measures have been used in several studies that were conducted in the adult population and demonstrated correlations between ulna length and height 16,17,19,22 . Furthermore, tape measures are cheaper and more accessible than anthropometric calipers 7,21,39 . We found good inter‐rater reliability using tape measures to assess ulna length (ICC = 0.86) and our equations and agreement were very similar to a study that used calipers 3 .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…However, tape measures have been used in several studies that were conducted in the adult population and demonstrated correlations between ulna length and height 16,17,19,22 . Furthermore, tape measures are cheaper and more accessible than anthropometric calipers 7,21,39 . We found good inter‐rater reliability using tape measures to assess ulna length (ICC = 0.86) and our equations and agreement were very similar to a study that used calipers 3 .…”
Section: Discussionsupporting
confidence: 78%
“…16,17,19,22 Furthermore, tape measures are cheaper and more accessible than anthropometric calipers. 7,21,39 We found good inter-rater reliability using tape measures to assess ulna length (ICC = 0.86) and our equations and agreement were very similar to a study that used calipers. 3 A considerable strength of the present study was, given that anthropometric parameters can differ by age and sex, 3,14,16,23,26 the predicted equations developed from the SuNDiAL project were ageand sex-specific and developed for New Zealand adolescents.…”
Section: Discussionsupporting
confidence: 77%
“…According to their results, the predicted mean tidal volume was 5.7ml/kg for males and 5.8 ml/kg for females. They did not include individuals aged more than 65 years [34].…”
Section: Discussionmentioning
confidence: 99%
“…At our institution, we have developed a measuring tape for the ulna (Figure 1) that directly reads off estimated height, PBW, and tidal volume (previously reported in this journal). 4 We validated this in a sample of 100 volunteers. This tape can be rapidly used at the onset of ventilation by one person without need to alter patient position.…”
Section: Jon Rivers and Jules Brownmentioning
confidence: 99%